2021
DOI: 10.5194/acp-21-5499-2021
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nighttime sulfuric acid from the ozonolysis of alkenes in Beijing

Abstract: Abstract. Gaseous sulfuric acid (SA) has received a lot of attention for its crucial role in atmospheric new particle formation (NPF). And for this reason, studies until now have mainly focused on daytime SA when most NPF events occur. While daytime SA production is driven by SO2 oxidation of OH radicals of photochemical origin, the formation of SA during nighttime and its potential influence on particle formation remains poorly understood. Here we present evidence for significant nighttime SA production in ur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Given a very short lifetime, the budget of H 2 SO 4 can be described by the following equation During the daytime, the H 2 SO 4 formation is dominated by the oxidation of SO 2 by OH, which is extremely difficult to be measured but has been demonstrated to be well reproduced by J (O 1 D) . During the nighttime, SO 2 oxidation by sCI and OH, produced from the ozonolysis of alkenes, is believed to control the formation of H 2 SO 4 . In polluted urban areas, alkenes have complex species, and it is generally impractical to make long-term, full-spectrum measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given a very short lifetime, the budget of H 2 SO 4 can be described by the following equation During the daytime, the H 2 SO 4 formation is dominated by the oxidation of SO 2 by OH, which is extremely difficult to be measured but has been demonstrated to be well reproduced by J (O 1 D) . During the nighttime, SO 2 oxidation by sCI and OH, produced from the ozonolysis of alkenes, is believed to control the formation of H 2 SO 4 . In polluted urban areas, alkenes have complex species, and it is generally impractical to make long-term, full-spectrum measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Gaseous H 2 SO 4 was long believed to be formed only from the reaction between SO 2 and OH. More recently, stabilized Criegee intermediates (sCI), formed in the ozonolysis of alkenes, were demonstrated to be able to oxidize SO 2 and contribute to gaseous H 2 SO 4 . , This was found to be particularly important for the nighttime H 2 SO 4 formation . In the coastal marine atmosphere, SO 2 oxidation by small Criegee intermediates (CI), produced possibly in photochemical reactions, and SO 3 formed from dimethyl sulfide (DMS) oxidation reaction with water might be non-negligible sources of H 2 SO 4 . ,, Recently, Olin et al indicated a potential source of H 2 SO 4 from traffic emissions in urban Helsinki based on the observed positive correlation between H 2 SO 4 and NO x concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…is a very reliable proxy for SA during the day (Lu et al, 2019). The ozonolysis of alkenes can form stabilized Criegee intermediates (SCIs) in addition to OH, and SCIs can also oxidize SO2 to form SA (Mauldin Iii et al, 2012;Guo et al, 2021). A previous study on SA proxy in this site has revealed that the reactions of SO2 with products from the ozonolysis of alkenes generate a moderate amount of nighttime sulfuric acid, with little effect on daytime sulfuric acid (Yang et al, 2021).…”
Section: Csmentioning
confidence: 92%
“…Secondary organic aerosols (SOAs), as an important and complex component of submicron particles (Zhang et al, 2007;Jimenez et al, 2009;Huang et al, 2014), are fully involved in affecting climate (IPCC, 2013) and causing health risks (Nel, 2005;Lim et al, 2012). Volatile organic compounds (VOCs) are ubiquitous in the atmosphere and are recognized as the main precursors of SOAs (Hallquist et al, 2009;Ziemann and Atkinson, 2012). However, the missing intermediate processes from VOCs to SOAs are yet to be elucidated (Hallquist et al, 2009;Ehn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Volatile organic compounds (VOCs) are ubiquitous in the atmosphere and are recognized as the main precursors of SOAs (Hallquist et al, 2009;Ziemann and Atkinson, 2012). However, the missing intermediate processes from VOCs to SOAs are yet to be elucidated (Hallquist et al, 2009;Ehn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%